Software engineering for modern Web applications : methodologies and technologies - Brandon, Dan, 1946 (Hershey, PA : Information Science Reference, 2008)
"This book presents current, effective software engineering methods for the design and development of modern Web-based applications"--Provided by publisher
"Premier reference source"--Cover
Includes bibliographical references and index
1
Keywords: Application software -- Development; Internet programming; Software engineering; Web site development